Perencanaan Strategis Sistem Informasi untuk Mendukung Keputusan Organisasi dengan Ward dan Peppard - Saputra, Yogi; Putri, Novianti Indah; Nurpajriah, Ela Siti; Jaelani, Dede; Hamdani, Alfinuur (Masoem University, 2023)
Ward and Peppard are used as the primary approach in planning information system strategies. This method involves identifying user needs, analyzing the business environment, evaluating information technology, and planning and implementing appropriate strategies. In the context of the Information Systems Study Program, this strategy will help improve the effectiveness of communication, information management, and appropriate decision-making. The research will analyze SWOT, value chain and Five Forces. The data collected will be analyzed and presented in a descriptive manner. The results of the research are expected to provide practical guidance for the Information Systems Study Program in planning and implementing effective information system strategies.The results of this research will make a positive contribution to the National University of the Republic of Indonesia Information System Studies Program in improving the efficiency and effectiveness of decision-making through the implementation of appropriate information system strategy.The aim of this study is to design and implement a decision-making information system strategy using the Ward and Peppard methodology in the Information Systems Study Program at the National University of the Republic of Indonesia. Preparing an effective information system stratega crucial factor in improving the efficiency and success of decision-making in an organization.